Tracing the evolution of accounting systems: a societal and human frameworks bibliometric study - Rana Airout (Future Business Journal)
Abstract This study explores the way accounting systems evolve across society and human environments over time, examining significant themes and trends. Based on bibliometric tools such as Web of Science Core Collection, Biblioshiny R package, and VOSviewer, we conduct keyword co-occurrence analysis on 271 articles within the 2010–2024-time frame. From the evidence, we find that studies increase each year by 4.94% with the highest contribution being from the USA and the spread of international collaborations. Seven thematic categories suggest areas like predictive accounting, allocation of resources, managerial conduct, environmental concerns, and human–computer interaction. The research uses exclusively bibliometric analysis to uncover historical trends in the field, ushering in themes of emergent nature including technology adoption, sustainability, and human-oriented approaches. The findings inform future paths of research and application of novel practices in accounting systems. Socially, the research uncovers how accounting systems address global challenges and bridge gaps between individuals, technology, and sustainability. It adds to our understanding of how accounting systems react to changing societal needs and complexities.